Apertura financiera y dolarización. Una perspectiva escéptica - Vernengo , Matías (2020)
The introduction of the Euro and the increasing economic convergence and integration of the NAFTA member-countries have stimulated a debate on the feasibility of adopting a common currency among Canada, the United States and Mexico. The project would certainly be that much more contentious since it is difficult to helieve that the U.S. will abandon the dollar and embrace a common currency. On the other hand the benefits from dollarization for American banks and multi-national firms would not be the case in a common currency arrangement, therefore to remark the differences between a monetary union and dollarization are of particular importance. Dollarization seems to export onc of the main problems of the American system to other economies, namely: the disproportional influence of financial interests and to the extent that investment is financed through these banks to those American multinational corporations the path growth of the country may be determined by the requirements of his own institutional structure.